2017
DOI: 10.1007/s11158-017-9363-4
|View full text |Cite
|
Sign up to set email alerts
|

The Choice Architect’s Trilemma

Abstract: Critics have long dismissed paternalistic choice architecture as conceptually muddled at best and oxymoronic at worst. In this article, I argue that this criticism remains true despite recent replies to the contrary. Further, I suggest that a similar conceptual criticism also applies to non-paternalistic choice architecture. This is due to a three-way tension between the effectiveness, avoidability, and distinctiveness of each nudge. To illustrate this tension, I provide a novel explanation of the mechanics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Illustratively, Floridi (2016) argues there is a trade-off between the effectiveness and the easy resistibility of nudges. A similar argument can be found in Mills (2018).…”
Section: Ethical Issue: Autonomysupporting
confidence: 82%
“…Illustratively, Floridi (2016) argues there is a trade-off between the effectiveness and the easy resistibility of nudges. A similar argument can be found in Mills (2018).…”
Section: Ethical Issue: Autonomysupporting
confidence: 82%
“…One defining condition of a nudge is that its effects must be easy for the targeted individual to reverse. Rebonato (2012; see also Mills, 2018) argued that nominal reversibilitythat is, reversibility in principleis not the same as reversibility in practice. He suggested that there may even be a trade-off between a nudge's effectiveness and its reversibility.…”
Section: Reversibilitymentioning
confidence: 99%
“…For instance, Sunstein (1996) argues, 'Many well-known anomalies in human behavior are best explained by reference to social norms and to the fact that people feel shame when they violate those norms' (p. 909). Mills (2018) has also contributed to this discussion, noting that the use of significant social incentives in nudging does not violate the concept of liberty as set out by J.S. Mill.…”
Section: Social Scorn and Stigmamentioning
confidence: 96%